Fundamentals of Rural Development: A Review Essay - Ahmad Mu'is; Lailatul Farida (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Extract In Fundamentals of Rural Development, Pattanaik examines rural transformation in contemporary India. Drawing on decades of empirical research, the book explores themes such as poverty alleviation, sustainable livelihoods, institutional reform, and participatory governance. Pattanaik integrates insights from development studies, economics, and rural sociology to challenge state-centric approaches, advocating for community-driven models rooted in local contexts. The book is organized into thematic sections covering historical foundations and urgent issues, including environmental degradation, gender disparities, and digital exclusion. Pattanaik engages with global discussions on neoliberal development, globalization, and ecological resilience, presenting a vision for rural futures that emphasizes human agency, equity, and sustainability. Similar to Ariyanto’s (2023) review of Scoones’ framework, this volume rejects technocratic oversimplifications and embraces complexity. As both a scholarly text and a practical guide, Fundamentals of Rural Development is an essential resource for researchers, development practitioners, and policymakers aiming to reimagine rural development beyond market-driven imperatives.